Smartphone charging using RFID / Mohamad Yusri Hanapi - Hanapi, Mohamad Yusri (2019)
This project presents a smartphone charging using Radio Frequency Identification (RFID) for performance analysis. RFID are microchips which can be attached to products in order to allow their contactless identification via radio frequency. Smartphone has become one of the most technologies that are frequently used by human beings to stay connected with other people. However, a frequent charging using plug can increase the power consumption and may result in electricity wastage especially in public places especially in library of UiTM Shah Alam. Therefore, a new approach for charging a smartphone is presented in this paper to optimize the number of people using smartphone charger and save power consumption. It is designed at a lower cost as possible to make it safe to use and energy efficient. In this paper, Atmega 328p acts as a microcontroller to ensure the system works smoothly and reducing the complexity of the schematic circuit. This smartphone charger works when the RFID card is successfully scanned and allows the user to choose how long the charge is charging.